Gastric Emptying Rate and Return Of Appetite In Lesser Spotted Dogfish, Scyliorhinus Canicula (Chondrichthyes: Elasmobranchii) - David W. Sims; Simon J. Davies; Quentin Bone (Journal of the Marine Biological Association of the United Kingdom, 1996)
The rates of gastric evacuation and return of appetite in adult Scyliorhinus canicula at 15°C were quantitatively assessed by serial x-radiographs of fish fed a moist diet containing radio-opaque glass beads, and by re-feeding trials. The evacuation of food from the cardiac stomach of dogfish was exponential in nature. Dogfish were fed small (~26 g of squid diet per fish) and large (~55g of squid diet per fish) meals and greater relative instantaneous rates of emptying occurred after consumption of small meals (k=0–0215) than larger meals (k=0·0086), indicating that the pattern of emptying was dependent on the degree of stomach fullness. There was inverse proportionality between rates of gastric evacuation (GE) and return of appetite (RA) after consumption of similar sized meals, with instantaneous rate coefficients being similar in magnitude (GE, k=0·0086; RA, k=0·0063). These results suggest that the rate of gastric evacuation is closely correlated with the return of appetite in S. canicula. An hypothesis is forwarded describing the possible physiological role of gastric evacuation rate in appetite regulation.